2016
DOI: 10.1007/s10459-016-9740-3
|View full text |Cite
|
Sign up to set email alerts
|

Social learning in a longitudinal integrated clinical placement

Abstract: Recent research has demonstrated that longitudinal integrated placements (LICs) are an alternative mode of clinical education to traditional placements. Extended student engagement in community settings provide the advantages of educational continuity as well as increased service provision in underserved areas. Developing and maintaining LICs require a differing approach to student learning than that for traditional placements. There has been little theoretically informed empirical research that has offered ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 61 publications
(108 reference statements)
1
84
1
Order By: Relevance
“…They argue that deriving a strategy from such a framework will help to achieve sustainability. An emphasis of the framework they used (Roberto and Levesque's Change Management Framework [35]) is on relationship building, which is appropriate in the context given that the LIC model has relationships at its core [1,4,5,[36][37][38][39][40][41][42][43][44]. Hudson et al [34] emphasized the importance of maintaining communication with all partners and stakeholders (supervisors, students, patients and healthcare providers) throughout and beyond the implementation and evaluation phases.…”
Section: Guideline 1: Manage Change Proactively With a Focus On Buildmentioning
confidence: 99%
“…They argue that deriving a strategy from such a framework will help to achieve sustainability. An emphasis of the framework they used (Roberto and Levesque's Change Management Framework [35]) is on relationship building, which is appropriate in the context given that the LIC model has relationships at its core [1,4,5,[36][37][38][39][40][41][42][43][44]. Hudson et al [34] emphasized the importance of maintaining communication with all partners and stakeholders (supervisors, students, patients and healthcare providers) throughout and beyond the implementation and evaluation phases.…”
Section: Guideline 1: Manage Change Proactively With a Focus On Buildmentioning
confidence: 99%
“…Students were uncertain of what was expected of them, and the short clinical placements made it difficult to become a part of the team. Students also described it as energy draining, and this may influence their education negatively because it has been shown that being included in the medical team, being allowed to participate and feeling that they belong are important for students’ learning in clinical environments . One reason why students do not feel confident in sharing experiences of emotional difficulties and feelings of uncertainty with their supervisors might be the short placements.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical years, longer rotations, or longitudinal integrated clerkships [31] provide mechanisms for peer networks and continuity of clinical supervision to support learning and personal development. Such approaches can increase the sense of connectivity that underpins wellbeing [32]. Offer progressive levels of challenge to prepare for troubling encounters:Challenges within a supportive and collegial environment should be deliberately built into the curriculum in a graduated fashion, and can be supported by simulation activities such as learning how to break bad news [33].…”
Section: Recommendationsmentioning
confidence: 99%
“…In the clinical years, longer rotations, or longitudinal integrated clerkships [31] provide mechanisms for peer networks and continuity of clinical supervision to support learning and personal development. Such approaches can increase the sense of connectivity that underpins wellbeing [32].…”
Section: Recommendationsmentioning
confidence: 99%